SISTEM PERANCANGAN ESTIMASI PENJUALAN EMAS MENGGUNAKAN METODE MOVING AVERAGE DAN METODE EXTREME STUDENTIZED DEVIATE - Leo, Sugiarto; Herwindiati, Dyah Erni; Lauro, Manatap Dolok (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
Every sale must have problem. For example, in recording transactions at stores that are not neat and structured, not knowing how much expenses and income at the store or predicting gold sales in the future. “Happy” Gold Shop is one of the shops that sell gold and solve this problem. Based on the above problems, it is necessary to make a gold sales estimation design application using the moving average method and the extreme studentized deviate method. The application is not only able to predict heavy sales but can record transaction data on each sale and purchase making it easier for owners to get sales data in a structured manner. The extreme studentized method is used to eliminate outlier values that are considered to deviate from the average value of a data. After correcting the outlier data, the data from the process will be used to predict sales in the form of daily estimates. Accuracy is based on an assessment of the MAD comparison using a period of two to five. The test results are based on the smallest MAD value for necklaces, bracelets and anklets with a period of 3,2,2 with a value of 11.47, 11.90 and 2.42